Lipoprotein Lpp and L, D-transpeptidases regulate the master regulator of virulence AggR in EAEC - Diana Rodriguez-Valverde; Nancy Leon-Montes; Laura Belmont-Monroy; Fernando Ruiz-Perez; Araceli E. Santiago (Scientific Reports)
Abstract Enteroaggregative Escherichia coli (EAEC) is a diarrheagenic pathotype associated with traveler’s diarrhea, foodborne outbreaks, and sporadic diarrhea in industrialized and developing countries. Regulation of virulence factors in EAEC is mediated by the master regulator AggR, an AraC/XylS family member controlling the expression of more than 44 genes associated with metabolism and virulence. Although the AggR regulon is well-characterized, the mechanism and upstream signaling cascades that regulate its activation are poorly understood. This study demonstrates that Lpp (Braun’s lipoprotein) and L, D-transpeptidases are required for AggR activation. We found that deletion lpp in EAEC resulted in the downregulation of more than 100 genes involved in transport, metabolism, and virulence. Among the genes, fourteen transcriptional factors, including AggR, were differentially expressed in 042Δlpp. Our findings also showed that Lpp anchoring to the peptidoglycan is a requisite for AggR-activation. Hence, chemical inhibition or genetic deletion of L, D-transpeptidases encoding genes involved in the crosslink of Lpp to the peptidoglycan abolished AggR activation. Moreover, the 042Δlpp mutant exhibited reduced biofilm formation on abiotic surfaces and reduced colonization of human intestinal colonoids. This is the first study to demonstrate the tight regulation of the AraC/XylS transcriptional regulator AggR, essential in EAEC virulence and intestinal colonization by components of the bacterial cell envelope.